1, 2, 3-Triazole substituted phthalocyanine metal complexes as potential inhibitors for anticholinesterase and antidiabetic enzymes with molecular docking studies. Issue 10 (21st June 2022) - Koçyiğit, Ümit M.; Taslimi, Parham; Tüzün, Burak; Yakan, Hasan; Muğlu, Halit; Güzel, Emre
Abstract: In recent years, acetylcholinesterase (AChE) and α-glycosidase (α-gly) inhibition have emerged as a promising and important approach for pharmacological intervention in many diseases such as glaucoma, epilepsy, obesity, cancer, and Alzheimer's. In this manner, the preparation and enzyme inhibition activities of peripherally 1, 2, 3-triazole group substituted metallophthalocyanine derivatives with strong absorption in the visible region were presented. These novel metallophthalocyanine derivatives (2-6 ) effectively inhibited AChE, with Ki values in the range of 40.11 ± 5.61 to 78.27 ± 15.42 µM. For α-glycosidase, the most effective Ki values of compounds 1 and 2 were with Ki values of 16.11 ± 3.13 and 18.31 ± 2.42 µM, respectively. Also, theoretical calculations were investigated to compare the chemical and biological activities of the ligand (1 ) and its metal complexes (2 –6 ). Biological activities of 1 and its complexes against acetylcholinesterase for ID 4M0E (AChE) and α-glycosidase for ID 1R47 (α-gly) are calculated. Theoretical calculations were compatible with the experimental results and these 1, 2, 3-triazole substituted phthalocyanine metal complexes were found to be efficient inhibitors for anticholinesterase and antidiabetic enzymes. Communicated by Ramaswamy H. Sarma